2021
DOI: 10.1111/bcpt.13657
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Epimedin B in treating osteoporosis as revealed by RNA sequencing‐based analysis

Abstract: With the ageing of populations, the management of osteoporosis is a priority of society in general. Epimedin B, a major ingredient of Herba Epimedii, which has the advantages of high content and hypotoxicity has been proved to be effective in preventing osteoporosis in vitro. However, the efficacy and mechanism of Epimedin B on osteoporosis in vivo have not been well elucidated yet. This study aimed to investigate the effects and the potential mechanisms of 8-week repeated oral administration of Epimedin B (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Thus far, only a few bioactivity or pharmacological studies on EB are available, and these studies describe the function of EB in osteoporosis treatment, nerve protection, and immune activity stimulation [ [20] , [21] , [22] ]. In this study, we provided comprehensive evidence of EB function in pigmentation in vivo and in vitro , using melanoma cells, human primary melanocytes, human skin-organ explant culture, and depigmented zebrafish and C57BL/6 mice; we also elucidated the multiple mechanisms regulating melanogenesis by increasing TYR expression, activity, and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, only a few bioactivity or pharmacological studies on EB are available, and these studies describe the function of EB in osteoporosis treatment, nerve protection, and immune activity stimulation [ [20] , [21] , [22] ]. In this study, we provided comprehensive evidence of EB function in pigmentation in vivo and in vitro , using melanoma cells, human primary melanocytes, human skin-organ explant culture, and depigmented zebrafish and C57BL/6 mice; we also elucidated the multiple mechanisms regulating melanogenesis by increasing TYR expression, activity, and stability.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 , 37 Meanwhile, Baohuoside I is one of the metabolites of Icariin in vivo and also one of the main active flavonoid components of the Epimedium brevicornum maxim . 38 Previous studies have shown that Curculigoside, the effective substance of Curculigo orchioides, could attenuate wear particle‐induced periprosthetic osteolysis by promoting osteoblastic MC3T3‐E1 cell differentiation and inhibiting osteoclast BMSC formation. 39 It is important to note that there is currently a lack of literature on the correlation between Orcinol glucoside and bone.…”
Section: Discussionmentioning
confidence: 99%
“…Sweroside interacts with membrane estrogen receptor-α and p38 pathway to promote osteoblastic differentiation and mineralization ( 35 ). Epimedin B downregulates PI3K-Akt, MAPK, and PPAR signaling pathways, which are mentioned above to result in bone destruction in mice ( 36 ) and have estrogen-like effects ( 37 ). Some other compounds like isopsoralen, asperosaponin VI, and neobavaisoflavone have also been proved to either enhance osteogenesis or inhibit osteoclast activation ( 38 42 ).…”
Section: Discussionmentioning
confidence: 99%